Eucalyptus Dilemma : a Clarification Thereof - Sharma, S. C.; Negi, J. D. S. (Indian Forester, 1985)
the paper summerises the impact of plantation foresty in general with special references to Eucalyptus plantation - a much talked about issue of the day. To be able to conserve the environment can-gained to the human inhabitation require the fuller understanding of mam-made ecosystem in terms of in-put and out-put in tatality. Of the many environmental factor which influences the human environment , in the present writeup, a possible role of nutrient dynamics has been detailed out. However, it is not easy to set the clock back early realisation of the facts must be analysed in its right perspective to save the humankind